Dampak Perubahan Pola Konsumsi Pangan Lokal Ubi dan Sagu Menjadi Pangan Beras di Kampung Makimi, Distrik Makimi, Kabupaten Nabire, Provinsi Papua - ROSDIANA BARANSANO; I WAYAN WINDIA; I DEWA PUTU OKA SUARDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
The Impact of Changes in Local Food Consumptionof Sweet Potato and Sago into Rice Food,in Kampung Makimi, Makimi District,Nabire Regency, Papua ProvinceThe impact of rice policy is a change in the pattern of local food consumption of thecommunity. This study aims to determine the impact of changes in the pattern ofconsumption of sweet potato and sago local food into rice food consumption. Thesampling method uses simple random sampling as many as 40 household headsfrom402 populations, theanalysis method used in this study is qualitative descriptive. Theresults showedthe impact of changes in the pattern of consumption of local food ofsweet potatoes and sago into rice consumption was a massive shift in publicconsumption resulted in a decrease in the level of preference for local sweet potato andsago food consumption. Most households prefer to consume rice food, because it tastesgood and is easily accessible. This can be seen by the amount of rice consumption asmuch as 1,443.8 kg / year, while the amount of sweet potato consumption is 182.4 kg /year, and sago is 728 kg / year. The negative impact of government policies andprograms on rice food availability has resulted in reduced production of local sweetpotatoes and sago. So the price of sweet potatoes and sago became expensive. Changesin the pattern of consumption of local foods of sweet potatoes and sago into riceresulted in an increase of 18.75% in Diabetes Meliatus in Makimi Makimi Village.Suggestion that can be submitted as input is that necessary to process local food intovalue-added commodities that can attract households to consume local food. Thegovernment is expected to formulate regulations related to the food sovereigntyprogram, especially local sweet potatoes and sago. Government policies for theassistance of raskin should be reduced by quota, and replaced by a food subsidiesprogram based on local food. There needs to be a tithe regarding the diversification ofconsumption of nutritiousbalanced food, especially in utilizing local food potential.